Highly Active and Reusable Kenaf Cellulose Supported Bio-Poly(hydroxamic acid) Functionalized Copper Catalysts for C–N Bond Formation Reactions - Siti Hajar, Mohamad Ros; Islam, Md. Shaharul; Lutfor, M. R.; Rashid, Shah Samiur; Chowdhury, Zaira Zaman; Ali, Md. Eaqub; Sarkar, Shaheen M. (North Carolina State University, 2017)
Distinctly active poly(hydroxamic acid) anchored copper (Cu) catalysts were synthesized from chemically modified kenaf cellulose. They were characterized by Fourier transform infrared spectroscopy (FT-IR), field emission scanning microscopy (FESEM), high resolution transmission electron microscopy (HRTEM), inductively coupled plasma atomic emission spectrometry (ICP-AES), UV-vis spectroscopy (UV), and X-ray photoelectron spectroscopy (XPS). The Cu-catalysts were successfully applied to the Michael addition reaction of amines with α,β-unsaturated carbonyl/cyano compounds and to the Click reactions of organoazides with alkynes under mild reaction conditions. The catalysts enabled excellent yields (88% to 95%) in both of the C–N bond formation reactions and showed easy recycling with outstanding reusability for seven cycles without any distinguished decrease in their catalytic activity.